Features of family disputes under english law - Глиняна, Катерина Михайлівна; Глиняная, Екатерина Михайловна; Hlyniana, Kateryna M. (My University, 2015)
The article discusses and analyzes the specifics of legal regulation of family disputes under legislation of England. It was stated that English law pays special attention to the judicial process of divorce, division of marital property and affairs that affect the direct interest of a child. In addition, in the article significant attention is paid to such settlement and resolution of family disputes, which can be carried out in alternative, extra-judicial means, such as negotiation and mediation. It was also considered the regularity and features of special state agencies, whose competence is settlement of disputes between members of family relations.

У статті розглянуто та проаналізовано особливості правового регулювання сімейних спорів за законодавством Англії. Так, було зазначено що англійське право приділяє особливу увагу судовому процесу розлучення, розподілу сімейного майна та справам, які безпосередньою впливають на інтерес дитини. Крім того, у статті важливу увагу приділено такому регулюванню та вирішенню сімейних спорів, яке може здійснюється альтернативними, позасудовими способами, такими як переговори та медіація. Також було розглянуто порядок та особливості спеціальних державних установ, до компетенції яких входить регулювання спорів між учасниками сімейних правовідносин

В статье рассматриваются и анализируются особенности правового регулирования семейных споров Англии. Так, акцентируется внимание на то, что английское право обращает особое внимание судебному процессу расторжения брака, разделу имущества между супругами, который непосредственно затрагивает интересы ребенка. Кроме того, в статье особое внимание уделено такому регулированию рассмотрения семейных споров которое осуществляется альтернативными внесудебными способами, такими как медиация. Так же было рассмотрено порядок и особенности специальных государственных учреждений, в компетенцию которых входит регулирование споров между участниками семейных правоотношений.
Hlyniana K. M. Features of family disputes under english law / K. M. Hlyniana // Часопис цивілістики. – 2015. – Вип. 19. – С. 166-169.
Keywords: family law; civil law; children’s rights; the judicial system; features of the consideration of family disputes; divorce; mediation; juvenile justice; сімейне право; цивільне право; права дитини; судова система; особливості розгляду сімейних спорів; розірвання шлюбу; медіація; ювенальна юстиція; семейное право; гражданское право; гражданский процесс; права ребенка; судебная система; особенности рассмотрения семейных споров; расторжение брака; медиация; ювенальная юстиция